GNAQ and GNA11 mutant nonuveal melanoma: a subtype distinct from both cutaneous and uveal melanoma. (1st November 2020) - Livingstone, E.; Zaremba, A.; Horn, S.; Ugurel, S.; Casalini, B.; Schlaak, M.; Hassel, J.C.; Herbst, R.; Utikal, J.S.; Weide, B.; Gutzmer, R.; Meier, F.; et al.
Summary: Background: GNAQ and GNA11 mutant nonuveal melanoma represent a poorly characterized rare subgroup of melanoma with a gene mutation profile similar to uveal melanoma. Objectives: To characterize these tumours in terms of clinical behaviour and genetic characteristics. Methods: Patients with nonuveal GNAQ / 11 mutated melanoma were identified from the prospective multicentre tumour tissue registry ADOREG, Tissue Registry in Melanoma (TRIM) and additional cooperating skin cancer centres. Extensive data on patient, tumour and treatment characteristics were collected retrospectively. Targeted sequencing was used to determine tumour mutational burden. Immunohistochemistry staining was performed for programmed death‐ligand 1 and BRCA1‐associated protein (BAP)1. Existing whole‐exome cutaneous and uveal melanoma data were analysed for mutation type and burden. Results: We identified 18 patients with metastatic GNAQ / 11 mutant nonuveal melanoma. Tumours had a lower tumour mutational burden and fewer ultraviolet signature mutations than cutaneous melanomas. In addition to GNAQ and GNA11 mutations (nine each), six splicing factor 3b subunit 1 ( SF3B1 ), three eukaryotic translation initiation factor 1A X‐linked ( EIF1AX ) and four BAP1 mutations were detected. In contrast to uveal melanoma, GNAQ / 11 mutant nonuveal melanomas frequently metastasized lymphatically and concurrent EIF1AX, SF3B1 and BAP1 mutations showed no apparent association with patient prognosis. Objective response to immunotherapy was poor with only one partial response observed in 10 treated patients (10%). Conclusions: Our findings suggest that GNAQ / 11 mutant nonuveal melanomas are a subtype of melanoma that is both clinically and genetically distinct from cutaneous and uveal melanoma. As they respond poorly to available treatment regimens, novel effective therapeutic approaches for affected patients are urgently needed. What is already known about this topic? The rare occurrence of GNAQ / 11 mutations in nonuveal melanoma has been documented. GNAQ / 11 mutant nonuveal melanomas also harbour genetic alterations in EIF1AX, SF3B1 and BAP1 that are of prognostic relevance in uveal melanoma. What does this study add? GNAQ / 11 mutant nonuveal melanomas show metastatic spread reminiscent of cutaneous melanoma, but not uveal melanoma. GNAQ / 11 mutant nonuveal melanomas have a low tumour mutational burden that is higher than uveal melanoma, but lower than cutaneous melanoma. What is the translational message? Primary GNAQ / 11 mutant nonuveal melanomas are a subtype of melanoma that is clinically and genetically distinct from both cutaneous and uveal melanoma. As metastatic GNAQ / 11 mutant nonuveal melanomas respond poorly to available systemic therapies, including immune checkpoint inhibition, novel therapeutic approaches for these tumours are urgently needed. Linked Comment:  Rafei‐Shamsabadi. Br J Dermatol 2020; 183 :806–807 .